Factors Influencing 5G Smartphone Purchase Intentions in Vietnamese Market: A Critical Realism Approach - Le , Minh-Duy; Ou Yang , Shirley (Journal of Marketing Development and Competitiveness, 2021)
The current debates on the fifth-generation (5G) have kindled a survival race to achieve it, but little attention has been paid from the customers’ perspectives themselves. This research, thus, aims to propose what will induce customers to purchase 5G smartphones. To this end, we performed a mixed-method study under the critical realism paradigm. In addition to common factors (e.g. social influences, product features, price, and aesthetic values), we also found that purchase intentions are negatively affected by security concerns, thus contributing a fresh perspective to literature. Besides, we used qualitative data to discover generative mechanisms that cause structural relationships.